1989
DOI: 10.1111/j.1432-1033.1989.tb14507.x
|View full text |Cite
|
Sign up to set email alerts
|

Characterization and application of a thermostable primary transport system: Cytochrome‐C oxidase from Bacillus stearothermophilus

Abstract: Cytochrome-c oxidase from Bacillus stearothermophilus has been purified to homogeneity by detergent extraction followed by DEAE-cellulose, hydroxyapatite-and gel-filtration chromatography. The enzyme is a typical cytochrome-aa3-type oxidase which binds carbon monoxfde and is sensitive to classical oxidase inhibitors like cyanide and azide. The purified enzyme is composed of three different subunits (57, 37 and 22 kDa). The subunit with intermediate molecular mass contains a covalently attached heme-c moiety. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
22
0

Year Published

1990
1990
2010
2010

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(22 citation statements)
references
References 46 publications
0
22
0
Order By: Relevance
“…Since the proton motive force was found to be a major driving force for amino acid transport, the influence of the medium composition on the Ap was studied. In previous publications de Vrij et al (9,10) demonstrated that in potassium phosphate (pH 6.0), oxidation via the respiratory chain of the electron donor ascorbate-TMPD results, in B. stearothermophilus membrane vesicles, in the generation of a high membrane potential (Aj = -105 mV) and a pH gradient (-ZA&pH = -45 mV). Qualitative information about the membrane potential generated has been obtained with the indicator diSC (3) to an interconversion of membrane potential into a pH gradient.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Since the proton motive force was found to be a major driving force for amino acid transport, the influence of the medium composition on the Ap was studied. In previous publications de Vrij et al (9,10) demonstrated that in potassium phosphate (pH 6.0), oxidation via the respiratory chain of the electron donor ascorbate-TMPD results, in B. stearothermophilus membrane vesicles, in the generation of a high membrane potential (Aj = -105 mV) and a pH gradient (-ZA&pH = -45 mV). Qualitative information about the membrane potential generated has been obtained with the indicator diSC (3) to an interconversion of membrane potential into a pH gradient.…”
Section: Resultsmentioning
confidence: 99%
“…Uptake of L-alanine (2.87 ,uM) or L-leucine (1.43 I1M) was measured at 45°C in oxygen-saturated 50 mM MES-NaOH (pH 6.0) containing 10 mM MgSO4. The figure shows L-alanine and L-leucine uptake in the absence of electron donors (0), in the presence of the electron donors ascorbate (20 mM) and TMPD (300 ,uM) without ionophores (0), and in the presence of monensin (20 nM) (L) or nonactin (10 membrane (ApH; interior alkaline) were determined at 45°C from the fluorescence changes of pyranine (excitation at 460 nm and emission at 508 nm [7,8] (20 mM) and TMPD (100 to 300 FuM). Monensin and nonactin were used at the final concentrations given above.…”
Section: Methodsmentioning
confidence: 99%
“…The inactivation temperature (T i ) can be defined as the temperature when the half-life t 1/2 of thermal denaturation is equal to 10 minutes [80], [82], [126]. The value of T i can be found by regression analysis of the line when the log 10 (t 1/2 ) values versus temperature are plotted.…”
Section: Methodsmentioning
confidence: 99%
“…Similar aa3-type oxidases with 3 subunits have been purified from Bacillus subtilis [4]. Bacillus stearothermophilus [5], Bacillus firmus [6] and Paracoccus denitrificans [7]. As the original preparation of the Paracoccus envme consists of two subunits [8,9], the reported two-subunit aa3-type oxidases of bacteria (see [ 10,l I] for reviews) may have lost the third subunit.…”
Section: Introduction Bacterial Cytochrome Aaandpementioning
confidence: 99%